Heat Therapy to Reduce Chest-Pain Among Patients with Acute Coronary Syndromes (ACS): A Literature Review - Aan Nur'aeni; Yanny Trisyani; Donny Nurhamsyah; Oman Hendi; Rahmalia Amni; Vanny Leutualy; Gita Maya Sari; Nurlaeci Nurlaeci; Rika Winarni (Padjadjaran Acute Care Nursing Journal, 2020)
The main clinical manifestations of patients with Acute Coronary Syndrome (ACS) during the acute period is chest pain. Handling complaints of pain patients with ACS definitively done with medication; however, it is possible to do additional nonpharmacological therapies to optimize the results. Nonpharmacological treatment can be performed in various ways, one of them with heat therapy. This literature review aimed to determine the use of heat therapy as an additional nonpharmacological intervention in reducing the intensity of chest pain in patients with ACS. Four electronic databases were used to carry out systematic searches on articles, namely Proquest, Science Direct, Pubmed, and CINAHL-Ebsco. The combination of keywords was "heat therapy" AND "chest pain" AND "acute coronary syndrome" NOT "Literature review" OR "Literature review" OR "Overview" OR "Systematic Review" OR "Meta-analysis." The inclusion criteria used were experimental study articles, peer-reviewed articles, and research articles written in English and performed in the period between 2014-2019. The search results obtained three articles that met the inclusion criteria and analyzed. The results of the study found that heat therapy effective in reducing the intensity of chest pain, the use of analgesic opioids, and improving the patient's hemodynamics. In conclusion, the therapy can be considered used as adjunctive therapy to reduce chest pain in patients with ACS with certain criteria. In addition, further research is also needed to see the effectiveness of this therapy if it is implemented with more frequent frequencies and compare its effectiveness in reducing chest pain if the application is given to the anterior or posterior of the chest.